Protective effect of paraoxonase 1 gene variant L55M in retinal vein occlusion - Ortak, Huseyin; Söğüt, Erkan; Ateş, Omer; Erkorkmaz, Unal; Benli, Ismail; Akbas, Ali; Demir, Selim; Ozyurt, Hüseyin (Molecular vision, 2013)
To determine if the paraoxonase 1 L55M and paraoxonase 1 Q192R gene polymorphisms have an effect on the risk of having a retinal vein occlusion (RVO). This case-control prospective study included 120 patients with RVO and 84 control subjects. All subjects were screened for age, gender, hypertension, diabetes, body mass index, fibrinogen, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triglycerides, total cholesterol, and very low-density lipoprotein. Subjects were also questioned about their smoking habits. Genomic DNA was extracted from peripheral leukocytes from EDTA anticoagulated blood. Genotyping of the paraoxonase 1 L55M and paraoxonase 1 Q192R polymorphisms was performed using real-time PCR. The frequency of the paraoxonase 1 (PON1) 55 LL genotype was significantly lower in patients with RVO than in the control subjects (28% versus 55%; p = 0.005). Logistic regression analyses were also conducted. After adjusting for gender, diabetes, hypertension, plasma fibrinogen levels, and high-density lipoprotein cholesterol, the lower LL genotype was found to be an independent predictor of RVO (β = 1.755; odds ratio = 5.783; p < 0.001; 95% confidence interval = 2.579-12.967). Subjects with a lower frequency PON1 55 LL genotype had a higher risk of RVO. These results indicate that paraoxonase gene polymorphisms may be a possible risk factor for RVO. We suggest that the LL genotype may have a protective role in the pathogenesis of RVO in the Turkish population.